The Influence of Management Information Systems, Transformational Leadership, and School-Based Management on the Quality of Educational Services in Elementary Schools in Boja District - Hindun Hindun; Titik Haryati; Ghufron Abdullah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The objectives of this research are to determine the effect of management information systems, transformational leadership, and school-based management on the quality of educational services in elementary schools in Boja District. This research uses a quantitative approach of the ex-post facto type. The population in this study was all elementary school teachers in the Boja District, Kendal Regency, totaling 138 people. The sampling technique used was proportionate random sampling, resulting in a sample of 103 teachers. Data collection was conducted using a questionnaire. Data sources consist of primary data (sourced from questionnaires) and secondary data (sourced from books, journals, and elementary school archives in the Boja District). Data analysis techniques include Partial Correlation Analysis, Multiple Regression Analysis, Hypothesis Testing, Determination Coefficient Test (R2), Structural Test, Effective Contribution, Relative Contribution, and Relative Contribution (SR) and Effective Contribution (SE). The research results show (1) There is an influence of management information systems on the quality of elementary school education services in Boja District of 76.4% with the highest contribution from the management information system dimension of 0.830 (83.0%), while the lowest dimension is system quality of 0.517 (51.7%), (2) There is an influence of transformational leadership on the quality of elementary school education services in Boja District of 76% with the highest contribution from the dimension that influences the highest transformational leadership from the intellectual stimulation dimension, namely 0.718 (71.8%). While the lowest dimension is Individualized influence of 0.474 (47.4%), (3) There is an influence of school-based management on the quality of elementary school education services in Boja District. of 79.3% with the highest contribution from the dimension that influences school-based management is the process dimension, namely 0.820 (82.0%). While the lowest dimension is educational input of 0.539 (53.9%). 4) There is an influence of management information systems, transformational leadership, and school-based management on the quality of elementary school education services in the Boja District of 84.4% with the highest contribution from the school-based management dimension of 79.3% and the lowest from the transformational leadership dimension of 76%.